Pseudo-Szabo operators and lightlike Szabo hypersurfaces - ATINDOGBE, COMLAN CYRIAQUE; LUNGIAMBUDILA, Oscar; TOSSA, JOEL (My University, 2011)
In this paper, the pseudo-inversion of degenerate metric is considered. We extend Szabó operators associated to algebraic covariant derivative curvature maps (tensors) to lightlike hypersurfaces. Some examples are given with explicit determination of their Szabó operators. Finally, we introduce the notion of lightlike Szabó hypersur- faces and give some characterization results of locally symmetric lightlike hypersurfaces and semi-symmetric lightlike hypersurfaces from Szabó condition.
Keywords: Algebraic covariant derivative curvature tensor; ∇-admissible screen distribution; Lightlike Szabó hypersurface.